Convergence considerations in moment-method analysis of a class of microstrip antennas - Chatterjee, D.; Plumb, R.G. (1997 IEEE Antennas and Propagation Society Meeting, 1997)
Inclusion of the probe-to-patch attachment mode current in the full-wave analysis of probe-fed microstrip antennas showed superior agreement with input impedance measurements. The attachment mode can be represented by the infinite eigenfunction or residue series, which are mutually different across the Stokes regions. It is shown that the residue series has better convergence properties and hence can be used to develop efficient moment-method algorithms for such antenna configurations.